2020
DOI: 10.1186/s13287-020-01904-3
|View full text |Cite
|
Sign up to set email alerts
|

hUMSCs regulate the differentiation of ovarian stromal cells via TGF-β1/Smad3 signaling pathway to inhibit ovarian fibrosis to repair ovarian function in POI rats

Abstract: Objective The basic pathological changes of primary ovarian insufficiency (POI) include ovarian tissue fibrosis and follicular development disorders. The human umbilical cord mesenchymal stem cell (hUMSC) transplantation has been shown an effective method to improve the ovarian function in POI rat model; however, the exact mechanisms are still unclear. The purpose of this study is to investigate whether the recovery of ovarian function in POI rats is related to the inhibition of tissue fibrosis following hUMSC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 47 publications
4
42
0
1
Order By: Relevance
“…In our study, Masson staining showed that the degree of fibrosis was significantly decreased after BMMSC treatment. Previous studies have shown similar effectiveness of MSCs in inhibiting ovarian fibrosis [ 20 , 36 ], and the mechanism involves mainly MSC-mediated inhibition of inflammatory factors [ 37 ]. These results suggested that BMMSCs inhibit the inflammatory response by secreting various immune and inflammation regulatory factors to reduce the degree of ovarian fibrosis.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, Masson staining showed that the degree of fibrosis was significantly decreased after BMMSC treatment. Previous studies have shown similar effectiveness of MSCs in inhibiting ovarian fibrosis [ 20 , 36 ], and the mechanism involves mainly MSC-mediated inhibition of inflammatory factors [ 37 ]. These results suggested that BMMSCs inhibit the inflammatory response by secreting various immune and inflammation regulatory factors to reduce the degree of ovarian fibrosis.…”
Section: Discussionmentioning
confidence: 97%
“…TGF-β1 from endometriomas modulates TGF-β1/Smad signaling pathway to promote brosis and adhesion to ovary [30]. TGF-β1/Smad3 pathway participates in ovarian brosis inhibition and results in ovarian function restoration in primary ovarian insu ciency (POI) rats after human umbilical cord mesenchymal stem cell (hUMSC) transplantation [31]. Whereas, whether PPARγ/TGF-β1/Smad signaling is implicated in ovarian brosis and dysfunction of PCOS is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that EVs could gather around the damaged GCs, and inhibit their apoptosis to restore ovarian secretory function (Zhang et al, 2020). Liu et al (2020) showed that MSCs-EVs could regulate the PI3K/AKT signaling pathway to enhance ovarian function. Notably, EVs could regulate proliferation-related pathways to modulate the state of ovarian cells, thus restoring ovarian reserve.…”
Section: New Approaches Based On Mscs (Figure 3) Extracellular Vesicles Of Mscsmentioning
confidence: 99%
“…Currently, researchers intend to explore the antifibrotic effects of MSCs in POI treatment. A previous study showed that MSCs exerted an antifibrotic effect in the injured ovaries of POI rats by regulating the TGF-β1/Smad-3 signaling pathway after transplantation ( Cui et al, 2020 ). Although only a few studies have explored anti-fibrosis effects of MSCs, inhibition and reduction of fibrosis in tissues and organs by MSCs are important mechanisms for the therapeutic effect.…”
Section: Mechanism Of Mscs-based Treatment For Poimentioning
confidence: 99%